2015
DOI: 10.1007/82_2015_468
|View full text |Cite
|
Sign up to set email alerts
|

Arenavirus Quasispecies and Their Biological Implications

Abstract: The family Arenaviridae currently comprises over 20 viral species, each of them associated with a main rodent species as the natural reservoir and in one case possibly phyllostomid bats. Moreover, recent findings have documented a divergent group of arenaviruses in captive alethinophidian snakes. Human infections occur through mucosal exposure to aerosols or by direct contact of abraded skin with infectious materials. Arenaviruses merit interest both as highly tractable experimental model systems to study acut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 286 publications
(382 reference statements)
3
37
0
2
Order By: Relevance
“…Filtered alignments did not show substantial substitution saturation ( supplementary table S4 , Supplementary Material online) and no evidence of recombination. Previous studies indicated that recombination events at the 3′ end of GPC occurred in the ancestor of Northern American NW viruses ( Grande-Pérez et al. 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…Filtered alignments did not show substantial substitution saturation ( supplementary table S4 , Supplementary Material online) and no evidence of recombination. Previous studies indicated that recombination events at the 3′ end of GPC occurred in the ancestor of Northern American NW viruses ( Grande-Pérez et al. 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…The N mRNA is a major transcript made from the ambisense S segment of the RVFV/phlebovirus genome. Because viral ambisense RNA segments often contain large intergenic structures that presumably aid in the generation of mRNAs (30,31), we wished to determine whether RNAs from other viruses that use the ambisense approach to gene expression also stall XRN1 as part of their strategy for host interaction. Arenaviruses have a bipartite genome and use an ambisense approach to generate mRNAs from both the genomic and anti-genomic version of both segments (Fig.…”
Section: -Terminal Regions Of Arenavirus Transcripts Also Contain Stmentioning
confidence: 99%
“…As an RNA virus, Candid#1 exists as a quasispecies that contains genetic variants that have been shown to give rise to clonal isolates of differing virulence (30,31). Nonetheless, the attenuated phenotype of Candid#1 appears to be stable in research laboratories and throughout its limited use as a vaccine.…”
Section: K33s-gpc Rcan Retains K33s and F427i Upon Prolonged Passage mentioning
confidence: 99%